2022
DOI: 10.3390/ma15176096
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Key Properties of Phosphogypsum-Red Mud-Slag Composite Cementitious Materials

Abstract: Due to the low content of silicon and aluminum in red mud and the low reaction activity of red mud, when it was used to prepare composite cementitious materials, it was necessary to assist other aluminosilicates and improve their activity by certain methods. In this study, it was proposed to add slag to increase the percentage of silicon and aluminum in the system, and to improve the reactivity of the system through the activation effect of sulfate in phosphogypsum. The effects of slag and phosphogypsum conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In addition, the density of long needle-like or short columnar AFt [ 32 ] is significantly weakened. However, the number of fibrous amorphous C-(A)-S-H gels [ 32 , 48 ] increased in RS-25 compared with RS-0, whereas this was not observed in RS-60, indicating that the active SiO 2 in RS could react with Ca(OH) 2 by hydration to form C-S-H gels, but the amount that can participate in the reaction is limited, further confirming the low activity of RS. In addition, it was seen that when the rate of RS increased, a significant quantity of unreacted RS particles ( Figure 1 b) manifested itself in the sample, coating the surface of the hydration products and filling the pores.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the density of long needle-like or short columnar AFt [ 32 ] is significantly weakened. However, the number of fibrous amorphous C-(A)-S-H gels [ 32 , 48 ] increased in RS-25 compared with RS-0, whereas this was not observed in RS-60, indicating that the active SiO 2 in RS could react with Ca(OH) 2 by hydration to form C-S-H gels, but the amount that can participate in the reaction is limited, further confirming the low activity of RS. In addition, it was seen that when the rate of RS increased, a significant quantity of unreacted RS particles ( Figure 1 b) manifested itself in the sample, coating the surface of the hydration products and filling the pores.…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that PG was not completely consumed during the formation of AFt and there was still a surplus, even though PG was present throughout the entire hydration process. According to Ma et al, the SO 4 2− produced by PG may combine with the hexa-ligand [Al(OH)6] 3− to generate AFt, and the system’s reduced concentration of Al 3+ can encourage the dissolution of reactive Al 2 O 3 and increase the production of C-A-H and AFt [ 48 ], which can increase the RS-PG-OPC’s strength. Figure 12 illustrates that after 28 days of hydration, the intensity of the diffraction peak of AFt in RPO-5 was greater than that in RS-25, which was consistent with the active Al 2 O 3 in the RS playing a role in the hydration process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, many researchers are exploring effective utilization ways for PG to serve as an alternative cementitious material in concrete. PG was tried to prepare high-content PG concrete, and although its mechanical properties were reduced, the permeability resistance of concrete was qualified [14][15][16][17]. This approach not only reduces the reserves of PG, but also reduces the production and consumption of cement, promoting environmental sustainability and conserving natural resources.…”
Section: Introductionmentioning
confidence: 99%